The Strategies of Dormitory Supervisors in Fostering Religious Moderation Values among Cadets at the West Nusa Tenggara Campus of the Institute of Public Administration (IPDN) - Nina Amalia; Deddy Ramdhani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Dormitory-based supervision has a strategic role in shaping religious moderation values among cadets in governmental higher education institutions, yet empirical attention to this mechanism remains limited. This study aims to analyze the strategies employed by dormitory supervisors in instilling religious moderation values among cadets at the IPDN West Nusa Tenggara Campus, examine their implications for the formation of moderate attitudes, and identify the challenges encountered in the process. A qualitative descriptive case study design was employed. Participants were selected through purposive sampling and included cadets, dormitory supervisors, the Head of Cadet Affairs, and the Campus Director. Data were collected through semi-structured interviews, participant observation, and documentation, and were analyzed through data collection, data condensation, data display, conclusion drawing, and verification. The findings reveal that religious moderation is systematically fostered through integrated strategies, including role modelling, habituation, supervision and discipline, collective activities, and the Jarlatsuh system embedded in daily dormitory life. These strategies contribute to the internalization of moderation values reflected in tolerance, fairness, inclusivity, dialogical competence, and strengthened national commitment. However, implementation faces several challenges, including cadets’ heterogeneous backgrounds, the influence of social media and external environments, and tendencies toward identity-based grouping. The study concludes that dormitory supervision functions as an effective mechanism for internalizing religious moderation values and shaping cadet character in multicultural residential education settings. This study contributes to character education, educational leadership, and religious moderation discourse by highlighting the importance of structured supervision, exemplary leadership, habituation, and digital literacy strengthening in developing tolerant, inclusive, and nationally committed future public administrators.